Kebijakan Kriminal Tindak Pidana Illegal Logging Di Kabupaten Kepulauan Aru - Agusteyn, Moses; Hehanussa, Deassy Jacomina Anthoneta; Lewerissa, Yanti Amelia (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
The criminal act of illegal logging is a crime against forest destruction in terms of the forestry sector. Where the crime includes logging which is carried out in areas where the forest is used illegally or without permission from the government or the authorities. Currently in the Aru Islands, the crime of illegal logging is one of the most serious crimes and is difficult to eradicate. The purposes and uses of this thesis research are: 1) What are the forms of dealing with illegal logging crimes in the Aru Islands; and 2) What is the criminal policy for dealing with illegal logging in the Aru Islands.